1975
DOI: 10.1139/v75-352
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in the Reactions of Nitrosopiperidine Carbanions. Steric vs. Stereoelectronic Control

Abstract: The anion of N-nitroso-4-phenylpiperidine reacts with methyl iodide, carbon dioxide, and benzophenone to give solely the axial substitution product. A second methylation of the monomethyl derivative gave the 2,6-diaxial derivative. None of the isomer having trans methyl groups could be detected. This trans isomer dominates over cis by 75:25 at equilibrium. From a consideration of the steric interactions present in these nitrosamines, it can be concluded that they alone cannot explain the observed high stereose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Hence other factors must also be involved in the shieldings. I11 the N-nitroso derivative of piperidine where the dihedral angle between the N-N and the a C-H bonds is Oo, a value of A6(sy/i-anti) = -11.0 ppm was observed in 13Cnir whereas in 'Hmr this difference was only 0.03 p p~n (9). In this type of compound both the steric cnnipression model (9) and the electric field effect (20) have been invoked to explain the 13C shifts.…”
Section: The Results Given Inmentioning
confidence: 99%
“…Hence other factors must also be involved in the shieldings. I11 the N-nitroso derivative of piperidine where the dihedral angle between the N-N and the a C-H bonds is Oo, a value of A6(sy/i-anti) = -11.0 ppm was observed in 13Cnir whereas in 'Hmr this difference was only 0.03 p p~n (9). In this type of compound both the steric cnnipression model (9) and the electric field effect (20) have been invoked to explain the 13C shifts.…”
Section: The Results Given Inmentioning
confidence: 99%
“…48 Extreme care to minimize exposure is necessary when using any N-nitrosamine reagents. Based on work conducted by Fraser, 49 Seebach showed that 4-phenylpiperidinederived amide 85 undergoes lithiation and alkylation at the equatorial position to give 2,4-cis-piperidine 86 (Scheme 16B). 50 The stereochemical disparity in the alkylation of the N-nitroso and N-acyl examples suggested the organolithium intermediates were congurationally stable.…”
Section: Generation Structure and Reactivitymentioning
confidence: 99%
“…Thus it seems very likely that lithium bromide and lithium methoxide are present as impurities in the commercial samples of methyllithium used for these reactions. A recent paper has described problems arising in organic syntheses from the presence of lithium bromide in solutions of methyllithium supplied by the Ventron Corporation (10). reaction with water prior to addition of the Et30BF4.…”
Section: The Reaction Of Phzgemn(co)4come With Melimentioning
confidence: 99%